Respuesta :

Answer:

standard form is -3x + y = 18

x-intercept

-3x + 0 = 18

-3x = 18

x = -6

(-6, 0) is the x-intercept

Step-by-step explanation:

The x-intercept is the x-value when y = 0 ---> (x, 0) or the point where the line crosses through the x-axis.

To find the x-intercept, you can substitute/plug in 0 into "y" in the equation:

y = 3x + 18     Plug in 0 into "y" since y = 0, then isolate/get the variable "x" by itself

0 = 3x + 18       Now subtract 18 on both sides

-18 = 3x         Divide 3 on both sides to get "x" by itself

-6 = x              -6 is the x-intercept